2016
DOI: 10.1039/c6tc00599c
|View full text |Cite
|
Sign up to set email alerts
|

Trace level detection of nitroanilines using a solution processable fluorescent porous organic polymer

Abstract: Fax: +91 (0)755 409 2392; Tel: +91 (0)755 669 2378. †Electronic Supplementary Information (ESI) available: [Details of characterizations of the polymer, molecular structures of the analytes, limits of detection, solid-state contact mode detection of nitroanilines, EPR and computational investigations.]. SeeA solution processable conjugated porous organic polymer (POP) based on tetraphenyl-5,5dioctylcyclopentadiene (TPDC-DB) was employed for nitroaromatics sensing by amplified fluorescence quenching. A comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…The adsorption difference versus the nitroaniline concentration is shown in Figure 11b, which shows a linear relationship between the adsorption and the concentration. The low limit for the detected nitroaniline concentration is 3.125 × 10 −4 mg/mL, which is lower than some published results [29] and comparable to other's work [30].…”
Section: Detection Of Nitroaniline By Cecp@ptsupporting
confidence: 84%
“…The adsorption difference versus the nitroaniline concentration is shown in Figure 11b, which shows a linear relationship between the adsorption and the concentration. The low limit for the detected nitroaniline concentration is 3.125 × 10 −4 mg/mL, which is lower than some published results [29] and comparable to other's work [30].…”
Section: Detection Of Nitroaniline By Cecp@ptsupporting
confidence: 84%
“…There are no overlaps between the two spectra, indicating that the mechanism of TDPDB fluorescence sensing to I 2 and PA is the electron transfer rather than energy transfer mechanism (Table S1 and Figure S16). Stern‐Volmer plots, which indicated that the fluoreacence quenching is the combination of static quenching and dynamic quenching (Figure C) …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the detection of these explosives from soil and water becomes an interesting and challenging problem in the field of environmental chemistry. Among all the reported methods for sensing of explosives materials, the optical sensing method is found to be more sensitive, selective, and portable for the detection of explosives . The higher sensitivity and selectivity of fluorescent conjugated polymers is due to the presence of electron donating moieties, being responsible for enhancing the contact between the electron‐rich polymers and electron‐deficient explosives .…”
Section: Role Of Truxene System In Photocatalytic Processesmentioning
confidence: 99%
“…Among all the reported methods for sensing of explosives materials, the optical sensing method is found to be more sensitive, selective, and portable for the detection of explosives. [100][101][102] The higher sensitivity and selectivity of fluorescent conjugated polymers is due to the presence of electron donating moieties, being responsible for enhancing the contact between the electronrich polymers and electron-deficient explosives. [103,104] The starshaped truxene molecules are efficient building blocks for the construction of electron-rich π-extended-conjugated polymers.…”
Section: Application Of Truxenes In Micelles and For Detection Of Expmentioning
confidence: 99%